Davis, A History Of Britain, 1885-1939; Pugh, Britain Since 1789 - A Concise History - Kriegel, Abraham (Teaching History: A Journal of Methods, 2002)
These admirable surveys are written by scholars who have previously made singular contributions to the monographic literature of modem British history. Martin Pugh, Professor of Modem History at the University of Newcastle, is the author of works on David Lloyd George, electoral politics of the late nineteenth and twentieth century, and twentieth-century women’s history. The Oxford historian John Davis has written heretofore on the politics of metropolitan London. Each is familiar with the major revisionist interpretations of modem British studies and incorporates recent monographic research into their respective works.